The civic education of young people in the education system: a review of the normative and legal acts of the Republic of Kazakhstan - Myrzakhmetova, A.Zh.; Khlebnikov, I.D.; Ote, D.; Momosheva, N.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article gives an overview of the state policy in the sphere of civic education and education of the Republic of Kazakhstan. The normative-legal basis in the sphere of civic education of youth is analyzed, the main directions, forms and projects are defined. Civic education of youth plays a key role in the formation of active and responsible citizens capable of participating in the public and political life of the country. In the Republic of Kazakhstan, the issues of civic education occupy an important place in the educational system, which is reflected in several normative and legal acts aimed at the development and implementation of relevant programmes and activities. The article is devoted to a review of normative-legal acts of the Republic of Kazakhstan regulating the issues of civic education of young people. It analyses the main laws and regulations that define the goals, objectives and methods of civic education, as well as the mechanisms of their implementation in educational institutions. Special attention is paid to programmes and initiatives aimed at the formation of civic responsibility and legal culture of Kazakh youth. The purpose of the article is to identify the main directions and approaches to civic education in the educational system of the Republic of Kazakhstan, as well as to assess the effectiveness of existing normative and legal acts in this area.
Бiлiм беру жүйесiндегі жастарды азаматтық тәрбиелеу: Қазақстан Республикасының нормативтiк құқықтық актiлерiне шолу
Гражданское воспитание молодежи в системе образования: обзор нормативно- правовых актов Республики Казахстан
Keywords: Civic education; education; history teaching; textbooks; history of Kazakhstan; state policy; youth policy; citizenship; normative and legal support